Home blood pressure monitoring in France: Device possession rate and associated determinants, the Esteban study. Issue 12 (23rd September 2020) - Vallée, Alexandre; Gabet, Amélie; Grave, Clémence; Lelong, Hélène; Blacher, Jacques; Olié, Valérie
Abstract: Home blood pressure monitoring (HBPM) is increasingly being promoted in hypertension guidelines to improve hypertension management. Possessing a HBPM device could improve blood pressure (BP) control and prognostic impact. The aims of this study were to estimate the possession rate of HBPM devices in the French population and in hypertensive adults, and to investigate the determinants of possessing such devices at home. Cross‐sectional analyses were performed using data from the Esteban survey, which comprised a representative sample of the French population. Among the 2, 054 study participants, 673 had hypertension. Of these, 385 were aware they had it. Weighted logistic regressions were performed to investigate the factors (socioeconomic, clinical, drug treatment, and healthcare visits) associated with possessing a HBPM device. 20.9% of the study sample, 42.1% of those with hypertension, and 54% of those aware of their hypertension, possessed a HBPM device. Female gender (OR = 2.03, 95%CI [1.46; 2.60]), smoking (OR = 2.33, 95%CI [1.51; 3.15]), antihypertensive drugs (OR = 1.75, 95%CI [1.06; 2.44]), general practitioner (GP) visits (OR = 3.28, 95%CI [1.84; 4.68]), and diabetes (OR = 0.41 95% CI [0.14; 0.68]) were associated with possessing a HBPM device among those aware of their hypertension. Over 20% of the study population possessed a HBPM device at home. This proportion rose to one in two in those aware or their hypertension. Among the latter, possessing a device was positively associated with female gender, GP visits, and antihypertensive drug use. Increasing possession of HBPM devices in the hypertensive population could foster better management of the condition.